Metabolic disease in Nepal: A perspective - Pandey, A S (Kathmandu University Medical Journal, 2012)
Inborn errors of metabolism or metabolic diseases, are a group of genetically determined metabolic disorders that result in mental retardation or early death. The prevalence of IEM in various countries shows a prevalence varying between 1 in 800 to 1 in 5000. As the technology for detecting metabolites has become more advanced, studies utilizing more modern methods report a higher prevalence. There have been reports of a few Inborn errors of metabolisms in Nepal, but studies to gauge the prevalence of these disorders in the Nepalese population are lacking. With conflicting statistical numbers from different sources regarding mental retardation cases in Nepalese population and a substantial rate of consanguinity and inter caste marriages, it would be prudent to initiate some pilot studies to estimate the prevalence of a group of disorders that can be diagnosed through simple laboratory tests, to be followed by a screening programme depending upon the results. The presented review discusses the need for and the possibilities of screening for these errors for early intervention in Nepal. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6224 Kathmandu Univ Med J 2010;8(3):333-40